2011
DOI: 10.1016/j.agwat.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The economics of low pressure drip irrigation and hand watering for vegetable production in the Sahel

Abstract: Low pressure drip irrigation is being promoted in Sub Saharan Africa as an alternative to traditional methods of small scale irrigation of vegetables. The African Market Garden (AMG) is a horticultural production system for smallholders based on low-pressure drip irrigation combined with an improved crop management package. The agronomic and economic performance of the AMG is compared to two gardens irrigated manually with watering cans. One of these gardens is managed according to the same improved crop manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
0
25
0
1
Order By: Relevance
“…These systems ranged in size from 80 to 500 m 2 (for individual farmers) and up to several hectares in communal and cluster configurations. Although little analysis has been done to assess the effectiveness of the more than 2,000 systems installed, one controlled field trial of the AMG in Niger compared it to traditional practices and showed dramatically increased returns on labor, land, and water, as well as improved yields, especially during the long dry season (29). Throughout Niger, farmers who turned to drip irrigation kits and better management techniques to begin producing higher-value vegetable crops often used their new income to invest in labor-saving motorized pumps and to expand their businesses (30).…”
Section: Brief Historical Developmentmentioning
confidence: 99%
“…These systems ranged in size from 80 to 500 m 2 (for individual farmers) and up to several hectares in communal and cluster configurations. Although little analysis has been done to assess the effectiveness of the more than 2,000 systems installed, one controlled field trial of the AMG in Niger compared it to traditional practices and showed dramatically increased returns on labor, land, and water, as well as improved yields, especially during the long dry season (29). Throughout Niger, farmers who turned to drip irrigation kits and better management techniques to begin producing higher-value vegetable crops often used their new income to invest in labor-saving motorized pumps and to expand their businesses (30).…”
Section: Brief Historical Developmentmentioning
confidence: 99%
“…Low-cost drip irrigation (LCDI) has emerged as a means to address these challenges through increased water use efficiency, labour savings, and higher economic returns (Ngigi et al, 2005;Polak et al, 2003). A recent study (Woltering et al, 2011) quantified the time savings and economic gains associated with drip irrigation for smallholders. Fertilizers should be applied in a form that becomes available in synchrony with crop demand for maximum utilization of nutrients from fertilizers to enhance productivity (Boyhan et al, 2001).…”
Section: Issn: 2319-7706 Volume 6 Number 8 (2017) Pp 718-724mentioning
confidence: 99%
“…The capacity of localized irrigation systems to reduce consumption on agricultural land without undermining the provision of the water requirements needed by the crops has been widely demonstrated under laboratory conditions and on experimental plots. From Swaziland sugarcane (Merry, 2003) to Turkish olive groves (Çetin et al, 2004), from Uzbekistan cotton (Ibragimov et al, 2007) to Sahel market gardens (Woltering et al, 2011), the world is full of successful and promising examples of drip irrigation development. [AQ3] in Argentina.…”
Section: Drip Irrigation: Intended and Unintended Effectsmentioning
confidence: 99%